Prosthetic Rehabilitation of a Patient with Gastroesophageal Reflux Disease: 4-Year Followup - Ricardo Coelho Okida; Daniela Micheline dos Santos; Aljomar José Vechiato Filho; Agda Marobo Andreotti; Rodrigo Antonio de Medeiros; Marcelo Coelho Goiato (Case Reports in Dentistry)
The gastroesophageal reflux disease (GERD) is one of the main causes of dental erosion. The aim of this case presented is to describe the prosthetic rehabilitation of a patient with GERD after 4 years of followup. A 33-year-old male patient complained about tooth sensitivity. The lingual surface of the maxillary anterior teeth and the cusps of the upper and lower posterior teeth presented wear. It was suspected that the feeling of heartburn reported by the patient associated with the intake of sports supplements (isotonics) was causing gastroesophageal changes. The patient was referred to a gastroenterologist and was diagnosed with GERD. Dental treatment was performed with metal-free crowns and porcelain veneers after medical treatment of the disease. With the change in eating habits, the treatment of GERD and lithium disilicate ceramics provided excellent cosmetic results after 4 years and the patient reported satisfaction with the treatment.